“Efecto del Ácido indolbutírico y tipo de estaquilla en el enraizamiento de plukenetia loretensis (Ule, 1908), en la provincia de San Martín-Perú” - Ayvar Macedo, Juan Carlos (2015)
The test was carried out in the experimental nursery garden of the Research lnstitute of the Peruvian Amazon (llAP) - San Martín; using a completely randomized design with factorial arrangement of 4 x 3, with three replicates per experimental and twelve stakes attached. Cuttings for juvenile wild relativa of wild relativas bank Plukenetia llAP Gender were u sed. The work was to evaluate the rooting juvenile cuttings of Plukenetia loretensis (Ule • 1908), in the province of San Martin, under the effect of tour doses of acid -3 - índole butyric acid (O % , 0.2 %, O , 4% , 0.6 %) , and three types of juvenile cuttings (basal, intermediate and apical) using propagators sub irrigation. At the end of the test (30 days after established in the propagator), rooting percentages AIB at a dose of 0.2% with a 82.65 % and type of juvenile cuttings (middle) was obtained in overall, the species can be easily rooted for the work of clonal propagation. Keywords: Plukenetia /oretensis, Plukenetia, vegetativa propagation, rooting juvenile cuttings, middle, chamber sub irrigation.